On the characterization of USD/PhP exchange-rate fluctuation via tree-structured regression - Gamalo, Mark Amper (2001)
The adoption of most countries to a floating exchange rate destroyed the apparent safe haven enjoyed by international business. This expedited research on exchange rate determination to manage exchange rate exposure. Though significant results have been disclosed, most theories have been flagrantly violated. The tenet that researches presume does not seem to accord with the convoluted system of the market upon which exchange rates operate. There are some promising thoughts, however, that can be pondered upon for investigation. Frenkel (1983) wrote: "An alternative yardstick for measuring the degree of exchange-rate fluctuations would be a comparison with prices of other assets." Upon this, the proponent embarks on investigating the influence of the Philippine Stock Market indices in the fluctuation of exchange-rates using tree-structured regression. The paper also discusses cyclic behavioral patterns of each of the series as well as the degree of association of the indices with the exchange-rate. Delay parameters are estimated to determine if adjustments in one series are mirrored on another. Change-point analysis is employed to find points in the data where the variance has changed considerably. Finally, the paper gives insights on the significant variables affecting the fluctuation. Ultimately, this paper will reveal attractive insights on the chaotic behavior of USD/PhP exhange-rates worthwhile of future inquiry